Fashion Design Learning System: A Comprehensive Evaluation of Apparel Design Programs in Education and Training Institutions - Ria Rizkia Alvi; Babang Robandi; Achmad Hufad; Uyu Wahyudin; Ace Suryadi; Elih Sudiapermana (AL-ISHLAH: Jurnal Pendidikan, 2024)
The mismatch between graduate skills and labor market needs remains a challenge in education and training due to limited industry involvement in curriculum design. LPP Ariyanti’s Fashion Design Training Program stands out by producing work-ready graduates capable of entrepreneurship in fashion design. This study evaluates the program's learning system to understand its effectiveness. A qualitative descriptive approach was used, involving observation (checklist), interviews (guide), and document analysis (sheet). A purposive sampling method selected three informants: a marketing communication representative, a fashion instructor, and a training participant. Data analysis followed four steps: collection, reduction, presentation, and conclusion drawing. The program succeeded across all evaluated aspects. Raw inputs revealed participants with diverse educational backgrounds and ages, yet uniformly productive. Instrumental inputs included skilled instructors, a standards-aligned curriculum, and sufficient infrastructure. Environmental inputs involved engagement in events and institutional partnerships with government and industry. The process incorporated blended, participatory, and project-based learning, complemented by effective formative and summative evaluations. Outputs demonstrated improvements in participants’ cognitive, affective, and psychomotor abilities. Outcomes highlighted increased graduate incomes, though few participants have yet started their own businesses. The comprehensive design of LPP Ariyanti’s training program, integrating industry partnerships, effective teaching methods, and robust infrastructure, contributes to its success. However, further support is needed to encourage entrepreneurship among graduates. The Fashion Design Training Program at LPP Ariyanti effectively equips participants with skills for employment and entrepreneurship, offering a model for industry-aligned education.